Performance appraisal decisions and career mobility among teachers in public school : a case study - Gelatina, Anak Dom @ Ricky Tujoh (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study aims to explore the performance appraisal decisions among teachers that become the raters in the public school with their career mobility which is conducted through case study. There were four research objectives and as well as four research questions in order to develop and create path to the questions to be asked to the informants. Here, this study was conducted using qualitative method whereby mix-method were used. The methods are using open-ended questions and also through interview process. The study was conducted at one of the public school in Kuching where one set of interview questions were distributed one week before the actual interview session and also two sets of open-ended questions was successfully gathered two weeks after. The data were collected and analyzed by using using ATLAS.ti where this software is not analyze by to create a proper ways to keep the data in the proper arrangement. Demographic characteristics of the informants were put in the Tables. The findings show that there is positive reactions or perceptions of the informants regarding the topic that being study. Beside, this research also provide some recommendations and contributions in Chapter 5 where the Human Resource Practitioners or organization can apply in the future to become more succesfull or in order to develop their talents and decision making in performance appraisal especially the role of raters.